Estimating the Prevalence of Persistent Symptoms After Sars-Cov-2 Infection (Post-Covid-19 Syndrome): A Regional Cross-Sectional Study Protocol - Bachelet-Norelli, V (BMJ Publishing Group, 2025)
Introduction The COVID-19 pandemic, driven by the SARS-CoV-2 virus, has had a significant global impact, with over 775 million cases reported and more than 7 million deaths as of July 2024. In Chile, approximately 5.4 million people have been infected, with a substantial proportion experiencing persistent symptoms known as post-COVID-19 syndrome. This study aims to estimate the prevalence of post-COVID-19 syndrome in Punta Arenas, Chile, and to explore the associated symptoms, mainly focusing on psychological, physical and molecular impacts on the affected population. Methods and analysis This cross-sectional study will use stratified random sampling to select a representative sample of 282 adults from Punta Arenas. Participants eligible for the study are those who had tested positive for SARS-CoV-2 by reverse transcription-quantitative PCR between July 2022 and July 2023. Data collection will include comprehensive clinical assessments, psychological evaluations and laboratory analyses of inflammatory biomarkers. Standardised instruments will be used to ensure consistency and reliability in measuring persistent symptoms. Statistical analyses will include descriptive statistics, regression models and subgroup analyses to identify risk factors and the prevalence of post-COVID-19 syndrome. Ethics and dissemination The Human Research Ethics Committee of the Clinical Hospital of the University of Chile approved the study protocol (Memorandum No 007/2023). We will present the results in peer-reviewed publications and national and international professional and academic meetings. © Author(s) (or their employer(s)) 2025.